2003
DOI: 10.1159/000071949
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Antepartum Bed Rest on Offspring

Abstract: We studied the children of mothers who were confined to bed during pregnancy for more than 15 consecutive days (mean 3.69 months) in the years 1986–1990 (bed rest offspring; BRO). We studied 86 children: 43 BRO and 43 control children. Data were obtained by means of a 20-item questionnaire filled in by the mothers. The BRO group differed from the control group in incidence of allergies (p = 0.005), motion sickness (p = 0.03), and need to be rocked to fall asleep (p = 0.01). More BRO born at term than controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Many studies have investigated the side‐effects of bed rest or activity restriction of pregnant women in hospital. There were physiological alterations, such as reduced gastrocnemius muscle function (Maloni & Schneider, 2002), low maternal weight gain (Maloni et al ., 1993), and behavioral alterations, such as more depressive symptoms and difficult infant behavior (Bellieni et al ., 2003). The experience of antepartum hospital bed rest was characterized by maternal anxiety and fear (Thornburg, 2002; Natori & Shimada, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the side‐effects of bed rest or activity restriction of pregnant women in hospital. There were physiological alterations, such as reduced gastrocnemius muscle function (Maloni & Schneider, 2002), low maternal weight gain (Maloni et al ., 1993), and behavioral alterations, such as more depressive symptoms and difficult infant behavior (Bellieni et al ., 2003). The experience of antepartum hospital bed rest was characterized by maternal anxiety and fear (Thornburg, 2002; Natori & Shimada, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The first is a question of fetal benefit from bed rest—the notion that the fetus will not be harmed during bed rest may lead to continued prescription of antepartum activity restriction, regardless of effects on maternal well‐being. Yet, some studies have shown definitive adverse neonatal effects, including low birth weight,10,17,29 and long‐term side effects in children whose mothers were on antepartum bed rest 69. Second, Schroeder suggests a fear of malpractice may lead to increased prescription of bed rest in an attempt to “do everything possible” for a high‐risk pregnancy, when, in fact, the literature does not support this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…studied long‐term effects on children born to mothers who had been placed on antepartum activity restriction. In their analysis, they found that offspring of mothers who had been on bed rest were significantly more likely to develop allergies, suffer from motion sickness, and require vigorous rocking to fall asleep 69. The authors hypothesize that perhaps bed rest leads to inadequate stimulation of the vestibular system during development while the mother decreases activity and ambulation.…”
Section: Potential Complicationsmentioning
confidence: 99%
“…We investigated 11-to 15-year-old children whose mothers had spent more than 15 consecutive days in bed during pregnancy [8]. Motion sickness was found to be more frequent in these children than in a control group (p !…”
Section: Copyright © 2004 S Karger Ag Baselmentioning
confidence: 99%